(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This study aimed to investigate the factors influencing poor breastfeeding practices among nursing mothers in this region. A cross-sectional survey was conducted, and data were collected from 265 women of reproductive age through structured questionnaires. The study revealed that the majority of respondents fell within the age range of 23 to 27 years (35.8%), were married (91.7%), and were of the Yoruba tribe (86.8%). Islam was the dominant religion (56.6%), and most participants had completed secondary education (60.0%). While the respondents exhibited good knowledge about breastfeeding (94.3%), there were significant gaps in breastfeeding practices, with only 73 (27.5%) of them exhibiting good practice. Several socio-demographic factors were found to be statistically associated with breastfeeding practice, including religion, level of education, occupation, estimated monthly income, and parity. Interestingly, respondents practicing Islam, students, and traders demonstrated higher rates of poor breastfeeding practice. Furthermore, respondents with lower estimated monthly incomes and higher parity (>4 children) also showed higher percentages of poor breastfeeding practices. These findings underscore the need for targeted interventions to promote breastfeeding practices among specific subgroups. Policy measures, workplace support, and community engagement are crucial in addressing these challenges and enhancing breastfeeding practices in Ibadan North East LGA. By implementing evidence-based strategies, healthcare providers, policymakers, and communities can work together to empower nursing mothers and optimize breastfeeding practices, ultimately contributing to the improved health and well-being of both mothers and infants in the region.